Physical chemical and biological quality test of spring in meurandeh - Lubis, Adelia Maisyaroh; Jayanthi, Sri; Setyoko, Setyoko; Pranata, Guswarni; Tanjung, Rizkan Azhari; Abadi, Muhammad Hafizi (STKIP Persada Khatulistiwa Sintang, 2024)
The spring in Meurandeh is a source of water that is widely used by residents as drinking water and natural medicine. This water is also often consumed raw without being processed. This study aims to determine the quality of the springs in Meurandeh. This type of research is descriptive qualitative with observational data collection methods. The data collected in this study was compiled, explained, and analyzed. Parameters tested include physical, chemical, and biological parameters. Physical parameters include odor, color, dissolved solids, and temperature. Chemical parameters include pH, hardness, iron, fluoride, DO, nitrate, nitrite, cyanide, detergent, and manganese. While the biological parameters are total Coliform and E.coli. Measurements of odor, dissolved solids, DO, temperature, and pH were carried out directly in the field. Tests for hardness, iron, fluoride, nitrate, nitrite, cyanide, detergent, manganese, total coliform, and E. coli were carried out at the Testing Laboratory of the Banda Aceh Center for Standardization and Industrial Services. The results showed that 14 of the 16 parameters tested met the requirements for drinking water quality according to the Minister of Health of the Republic of Indonesia Number 492 of 2010. Meanwhile, the other two did not meet these requirements, namely pH and total Colliform.